Synthesis of natural salicylic acid as a cosmetic ingredient using green chemistry methods - ALTURFAN, EBRU IŞIK (My University, 2022)
Objective: Salicylic acid (SA) is a keratinolytic agent also used as preservative in cosmetic products. Green chemistry, known as sustainable chemistry, is the design of products and processes eliminating the use of chemicals. It is applicable throughout a chemical product's life cycle, including its design, manufacture, use, and final disposal. The aim of this study was to synthesize SA with green chemistry methods using different amounts of wintergreen oil and to optimize the relevant steps in this path. Materials and Methods: The SA was synthesized from natural wintergreen oil using green chemistry methods. First laboratory-scale synthesis was developed and 15 laboratory-scale synthesis trial patterns, using reaction temperature, wintergreen oil-sodium hydroxide molar ratio, sodium hydroxide-water weight ratio, reaction time and pH were performed. Purity was analysed with gas chromatographymass spectrometry (GC-MS) and moisture analysis was performed. Results and Conclusion: As a result of pilot production run with 1 kg, 5 kg, and three batches of 20 kg of wintergreen oil, SA was produced with a yield range of 91.06-93.92 %. The resulting SA batches had a purity of approximately 99%. This is a sufficient degree of purity for SA to be used as a raw material in cosmetics products. Filtering the SA solution using a filter press reduced crystal drying time and brought down the total production time to eight days.
Keywords: Tıp; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Klinik Tıp; Doğa Bilimleri Genel; Farmakoloji ve Toksikoloji; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); CLINICAL MEDICINE; NATURAL SCIENCES, GENERAL; PHARMACOLOGY & TOXICOLOGY; MULTIDISCIPLINARY SCIENCES; Multidisciplinary; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Salicylic acid; green chemistry; wintergreen oil; cosmetic